2006
DOI: 10.5144/0256-4947.2006.105
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between thrombophilic mutations and preeclampsia: a prospective case-control study

Abstract: BACKGROUNDPreeclampsia and its association with thrombophilia remain controversial, due to inconsistent results in different studies, which include different ethnic groups, selection criteria, and patient numbers. The aim of this study was to determine the relationship between thrombophilia and preeclamptic patients in our region.METHODSIn a prospective case-control study, we compared 100 consecutive women with preeclampsia and eclampsia (group 1) with 100 normal pregnant women (group 2). All women were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…Among all studies, 42 studies were performed among East Asians [27], [28], [33], [37], [42], [43], [48], [50], [54], [56], [57], [60], [65], [73], [75], [78], [79], [81], [86]–[90], [94]–[97], [102], [103], [105]–[107], [115]–[118], [122], [124], [131], [132], [134], [136], 54 among Caucasians [29], [31], [32], [34], [35], [38][41], [44][47], [49], [51][53], [55], [59], [63], [64], [66], [67], [69]–[72], [74], [76], [77], [80], [82], [84], [92], [93], [98][101], [109], [110], [112]–…”
Section: Resultsmentioning
confidence: 99%
“…Among all studies, 42 studies were performed among East Asians [27], [28], [33], [37], [42], [43], [48], [50], [54], [56], [57], [60], [65], [73], [75], [78], [79], [81], [86]–[90], [94]–[97], [102], [103], [105]–[107], [115]–[118], [122], [124], [131], [132], [134], [136], 54 among Caucasians [29], [31], [32], [34], [35], [38][41], [44][47], [49], [51][53], [55], [59], [63], [64], [66], [67], [69]–[72], [74], [76], [77], [80], [82], [84], [92], [93], [98][101], [109], [110], [112]–…”
Section: Resultsmentioning
confidence: 99%
“…However, similar studies have not found a significant difference in mean levels of free protein S between the study groups, 2,20,21 probably because of differences in the study participants, in the period of sample collection, and in the assay methods. For example, Yalinkaya et al 21 analyzed samples collected during the postpartum period (8 weeks) and used a coagulation-based assay. The expected changes in the levels of these proteins, owing to the effects of pregnancy and pre-eclampsia, might have almost completely resolved by this stage.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation may result in thrombus formation in the placenta and thus may be a genetic risk factor for preeclampsia. 18,63,[66][67][68][69] However, many studies have controversial results about whether the FVL mutation is a genetic factor that involved in the development of HDP. For example, among all the studies in this meta-analysis, 15 of them get a negative result (GA + AA/GG, OR < 1.5) that the FVL mutation is not an important genetic involvement of HDP, 35 of them have the positive conclusion (GA + AA/GG, OR ≥ 1.5).…”
Section: Discussionmentioning
confidence: 99%